Visualization of implementation of advanced technologies in space 4D - Боровик, Виталий Сергеевич; Прокопенко, Юрий Евгеньевич; Боровик, Виталий Витальевич (Eastern-European Journal of Enterprise Technologies, 2014)
Graphical interpretation of the Cobb-Douglas production function (PF), which allows to visualize the combined influence of the main production factors was taken as the basis of the research. A mathematical model of the organizational-economic system management in conditions of scientific-technological progress, in which implementation is seen as an algebraic introduction of the resource differential system to PF is proposed. The model allows to calculate the implementation efficiency of advanced technology for real organizational-economic system, production activity of which, in addition to quantitative parameters, is also expressed by qualitative characteristics – production resource usage intensity. Based on the Lorentz transformation, as an analogy for Minkowski metric of orthogonal transformations, generalizing the concepts of motion in Euclidean space, an attempt to graphically present management under STP in fourdimensional space that unites the physical three-dimensional space and time was made. It is shown that a clear understanding of the management processes in implementing new technology in 4D space plays an important role not only due to great probative value, but also for understanding, evaluating and finding the optimal management.